2017
DOI: 10.1128/jvi.01913-16
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Adaptive Mutations during the West African Ebola Virus Outbreak

Abstract: The Ebola virus (EBOV) outbreak in West Africa started in December 2013, claimed more than 11,000 lives, threatened to destabilize a whole region, and showed how easily health crises can turn into humanitarian disasters. EBOV genomic sequences of the West African outbreak revealed nonsynonymous mutations, which induced considerable public attention, but their role in virus spread and disease remains obscure. In this study, we investigated the functional significance of three nonsynonymous mutations that emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 41 publications
2
69
3
Order By: Relevance
“…However, our studies do not support the suggestion that changes in residue 82 alter receptor affinity (Diehl et al, 2016; Dietzel et al, 2016; Urbanowicz et al, 2016). The recently obtained structure of GP bound to NPC1 revealed that the α-helix containing A82 is displaced by NPC1 binding, and it was proposed that this conformational change promotes the release of the internal fusion loop in GP2 (Wang et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our studies do not support the suggestion that changes in residue 82 alter receptor affinity (Diehl et al, 2016; Dietzel et al, 2016; Urbanowicz et al, 2016). The recently obtained structure of GP bound to NPC1 revealed that the α-helix containing A82 is displaced by NPC1 binding, and it was proposed that this conformational change promotes the release of the internal fusion loop in GP2 (Wang et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…This strongly predicts that V82 and I544 promote infection under conditions where expression of NPC1 and/or cathepsin B in target cells is low, such as in tissue monocytes and dendritic cells (DCs) in boundary tissues that are early targets for infection (Bray and Geisbert, 2005; Martinez et al, 2013). Expansion of infection in the host to cells where NPC1 and cathepsin B expression is low, as modeled by the use of 3.47 and CA074, may result in the reported increase in viremia associated with A82V (Diehl et al, 2016; Dietzel et al, 2016). A recent study found that Makona C07 containing T544 grows more slowly and is less virulent than 1976 Yambuku Ecran which, after cleavage, differs from Makona C07 solely by the presence of I544 in GP (Smither et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, R111C substitution in NP has been proposed to be signi¯cant in NP oligomerization, NC formation and VP40 interaction, by comparative analysis of the amino acid sequences of ebola viral proteins from 2013 to 2015. 48 Alanine (A) to serine (S) substitutions, A233S and A279S, are close to the cleft of NP for RNA binding. The serine residues involved in these substitutions (A233S, A279S and S365H) are potential phosphorylation sites on the NP proteins, surrounding the cleft where NP binds to ssRNA (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…48 It is also worth noting that changes in the conserved MTase region may add on to the increased pathogenicity (Table S2).…”
Section: Important Residue Variations Of Polymerase Lmentioning
confidence: 99%
See 1 more Smart Citation